(untitled) (Bangladesh Agronomy Journal, 2020)
The experiment was conducted at Sher-e-Bangla Agricultural University, Dhaka with the financial support of SAURES (Sher-e-Bangla Agricultural University Research System) to study the possibility of growing quinoa in Bangladesh with different sowing dates having two cultivars. The experiment comprised of two factors; Factor A: Cultivar (2) viz., Titicaca (C1) and Vikinga (C2) and Factor B: Sowing date (5) viz. November -10 (S1), December -10 (S2), January -10 (S3), February -10 (S4) and March -10(S5). The experiment was laid out in split-plot design with three replications. Results revealed that different growth parameters, yield attributes and yield were significantly varied with different sowing dates. At harvest, the tallest plant height (63.75 cm), highest seed yield (0.77 t ha-1) and straw yield (0.89 t ha-1) was found from Titicaca but the higher number of branches plant-1 (17.71) from Vikinga. The tallest plant height (62.54 cm), highest branch number plant-1 (22.82), longest inflorescence (29.62 cm), highest 1000-seed weight (2.56 g), seed yield (1.09 t ha-1), straw yield (1.25 t ha-1) and harvest index (46.58%) was exhibited by November -10 sowing. The interaction effect of Titicaca sown in November -10 (C1S1) resulted the highest plant height at harvest (72.83 cm), branches plant-1 (25.20), 1000-seed weight (2.58 g), seed yield (1.16 t ha-1) and straw yield (1.33 t ha-1) but the highest inflorescence length (31.46 cm) and harvest index (47.02%) from C2S2 (Vikinga sown in December – 10). From the above results it can be concluded that quinoa – as a new crop is suitable to cultivate in Rabi season of Bangladesh with a complete agronomic management package. Bangladesh Agron. J. 2020, 23(1): 67-73